Fostering Critical Thinking Skills: The Role of Simulations in Science Education - Karimi, Amir; Sari, Winda Purnama; Yassin, Abdulnassir (Buletin Edukasi Indonesia, 2024)
This article explores the role of simulations in enhancing critical thinking skills within the realm of science education. In today's rapidly evolving world, the ability to think critically is paramount, particularly in scientific fields where understanding complex concepts and navigating uncertainty are essential. Traditional instructional methods often fall short in promoting critical thinking, necessitating innovative approaches. Simulations offer dynamic, experiential learning opportunities that engage students in active problem-solving, decision-making, and collaborative exploration. By simulating real-world phenomena and laboratory experiments, simulations provide students with immersive experiences that foster deeper understanding and the application of scientific principles. This abstract encapsulates the importance of simulations in cultivating critical thinking skills and highlights their potential to shape the next generation of scientifically literate individuals.